I Hate the News May 13 - Dasgupta, Sunil (I Hate Politics Podcast, 2025)
Washington DC releases its 2025 homeless count, with significant improvement. Trump wants beautification, but where do the unhoused go? Mayor Muriel Bowser steps into the tipped wage debate again. MCPS Superintendent Thomas Taylor lays out the school district’s problems. With some talk of Larry Hogan running again for Maryland governor, Delegate Marc Korman talks about the new law changing conflict rules for Maryland governors that will affect Hogan if he returns. And more. Music by Arlington-based experimental music composer Pierre Bernasconi.
Keywords: I Hate Politics